Effects of functional training on sprinting, jumping, and functional movement in athletes: a systematic review - Bashir, Marrium; Soh, Kim Geok; Samsudin, Shamsulariffin; Akbar, Saddam; Luo, Shengyao; Sunardi, Jaka (Frontiers Research Foundation, 2022)
This systematic review aims to illuminate the effects of functional training on sprinting, jumping, and functional movements in athletes. A systematic search of electronic databases—that include PubMed, EBSCOhost (Sport Discus), SCOPUS, ProQuest, Google Scholar, and additional references—was carried out using keywords associated with functional training, jumping, sprinting, functional movement skills, and athletes, in compliance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement criteria. The Physiotherapy Evidence Database (PEDro) scale was used to measure the methodological quality of the studies included in the systematic review. Results: From a total of 220 studies, 15 included ones met all eligibility criteria and were scored between 4-5 points—considered as“ moderate quality”—by the PEDro scale. Most studies recorded positive effects of functional training on athletes’ sprinting, jumping, and functional movement. In contrast, a small number of studies did not find any positive effects of functional training on sprinting, squat jump, vertical jump, and countermovement jump due to the short duration and frequency of the training, as well as the lack of additional exercises that come with the interventions. Furthermore, the reviewed studies reveal that there is limited research within the literature on 5, 15, 25, and 50 m sprinting, squat jump, quadrant jump, and functional movement in athletes. Conclusion: Although the length of training interventions varied across studies in this systematic review, functional training interventions were found to help improve athletes’ performance. The review reveals that training duration, intensity, and frequency are some critical variables that need to be taken into account when developing a successful functional training intervention for athletes. More studies are required to evaluate the influence of different accessible functional training durations on athletes’ sprinting, jumping performance, and functional movement. Finally, further research needs to be done to investigate the impacts of functional training on performance and movement skills of male and female athletes at all levels in other sports. Systematic Review Registration: https://inplasy.com/inplasy-2022-5-0130/, identifier INPLASY202250130